2020
DOI: 10.1002/cam4.3544
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NUTM2A‐AS1 positively modulates TET1 and HIF‐1A to enhance gastric cancer tumorigenesis and drug resistance by sponging miR‐376a

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…However, the underlying molecular mechanism of the effects of NUTM2A-AS1 in lung cancer has not been reported, to the best of our knowledge. A previous study demonstrated that programmed death-ligand 1 partially rescued NUTM2A-AS1- and miR-376a-regulated gastric cancer (GC) cell tumorigenesis and drug resistance ( 30 ). In addition, miR-376a was recently identified to be associated with NUTM2A-AS1 and found to be critical for NUTM2A-AS1-induced tumorigenesis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the underlying molecular mechanism of the effects of NUTM2A-AS1 in lung cancer has not been reported, to the best of our knowledge. A previous study demonstrated that programmed death-ligand 1 partially rescued NUTM2A-AS1- and miR-376a-regulated gastric cancer (GC) cell tumorigenesis and drug resistance ( 30 ). In addition, miR-376a was recently identified to be associated with NUTM2A-AS1 and found to be critical for NUTM2A-AS1-induced tumorigenesis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that programmed death-ligand 1 partially rescued NUTM2A-AS1- and miR-376a-regulated gastric cancer (GC) cell tumorigenesis and drug resistance ( 30 ). In addition, miR-376a was recently identified to be associated with NUTM2A-AS1 and found to be critical for NUTM2A-AS1-induced tumorigenesis ( 30 ). Moreover, lncRNA realizes its function by regulating miRNA/mRNA expression ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, more and more evidence suggested that higher glycolysis may contribute to the development of drug resistance in multiple tumors, including TNBC. HIF-1α plays a critical role in the regulation of glycolysis of cancer cells, has been demonstrated to be related to chemoresistance in many kinds of cancer cells 46,47 . We demonstrated in this study that downregulation of ANRIL decreased HIF-1α-dependent glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α induces the expression of miR-27a, which is closely associated with MDR in GC ( Zhao et al, 2015 ). By binding to miR-376a, the lncRNA Nutm2a-AS1 positively modulates GC formation and drug resistance through the regulation of HIF-1α ( Wang et al, 2020c ).…”
Section: The Mechanism Of Resistance To Chemotherapy or Radiotherapy Of Ncrnas For Gastric Cancermentioning
confidence: 99%